Stability Enhancement of a Power System With a PMSG-Based and a DFIG-Based Offshore Wind Farm Using a SVC With an Adaptive-Network-Based Fuzzy Inference System - Wang, Li; Truong, Dinh-Nhon (IEEE transactions on industrial electronics (1982), 2013)
This paper presents the stability-improvement results of a synchronous generator (SG)-based one-machine infinite-bus system with a permanent-magnet SG (PMSG)-based offshore wind farm (OWF) and a doubly fed induction generator (DFIG)-based OWF using a static VAR compensator (SVC). The operating characteristics of the studied two OWFs are simulated by an equivalent aggregated PMSG driven by an equivalent wind turbine (WT) and an equivalent aggregated DFIG driven by an equivalent WT through an equivalent gearbox, respectively. A damping controller of the SVC is designed by using adaptive-network-based fuzzy inference system (ANFIS) to contribute adequate damping characteristics to the dominant modes of the studied SG under various operating conditions. A frequency-domain approach based on a linearized system model using root-loci technique and a time-domain scheme based on a nonlinear system model subject to various disturbances are both utilized to examine the effectiveness of the proposed control scheme. It can be concluded from the simulation results that the proposed SVC joined with the ANFIS damping controller is capable of improving the stability of the studied SG system subject to different disturbances.